Catching up on lost learning opportunities Research and policy evidence on key learning recovery strategies - Minea-Pic, Andreea (OECD Education Working Papers, 2023)
Climate change and natural disasters, the COVID-19 pandemic, and geopolitical shocks have increasingly disrupted school education around the world in recent years. Whether leading to school closures, school destructions or repeated interruptions in students' learning experiences, these external shocks have translated into lost learning opportunities for students. In this context, education systems face heightened pressure to become ever more resilient, enhance the efficiency of public spending and address emerging learning gaps. This working paper highlights key education strategies for helping students catch up on lost learning opportunities and bridge learning gaps, based on a review of research and policy evidence from OECD and non-OECD countries. It examines a range of academic strategies to address learning gaps, including i) adapting instructional strategies and pedagogies to individual needs, ii) extending and adapting the time of instruction, and iii) providing curricular flexibility and enabling fluid learning pathways within the school system. It provides research evidence on the effectiveness of such strategies, together with examples of their large-scale implementation and cost-effectiveness considerations. While this paper presents programmes of general interest for all countries, a separate policy brief targets learning recovery strategies for students in Ukraine